The Development of a Competency Assessment Standard for General Practitioners in China - Rao, Xin; Lai, Jinming; Wu, Hua; Li, Yang; Xu, Xingzhi; Browning, Colette Joy; Thomas, Shane Andrew (Frontiers in Public Health, 2020)
This paper describes the development of a competency assessment standard for General Practitioners in Shenzhen, China. The standard is to be used for developing and delivering the training curriculum for general practitioners. The requirement for the training of General Practitioners mandated by government policy requires an international competitive curriculum to meet the needs of patients and the community. A Delphi process was employed to arrive at a curriculum consensus. An expert panel and 14 working groups were established to review and evaluate national and international competency standards for General Practice and develop a set of standards, through a modified Delphi methodology. 43 stakeholders were involved in the project. The project resulted in a detailed curriculum statement. The curriculum was then used in 2017 and 2018 where pilot examinations of GP trainees (n=298 and n=315 respectively) were conducted to assess the trainee’s competencies against the Standards. The examination included two modules, a written test (Module A) and a practical test (Module B). The success rate for participants was relatively low with the majority not successfully completing the assessments. The assessments will be further refined in subsequent work.